A small choreography of the wild woman: female experience in Pequena coreografia do adeus - Dalava, Lucas Almeida [UNESP]; Pires, Antonio Donizeti [UNESP] (Univ Estadual Paulista-unesp, 2022)
This article tries to interpret the novel Pequena coreografia do Adeus (2021), by Aline Bei, in the light of psychoanalysis, considering, for that purpose, the theories related to the female psyche elaborated in Women who run with the wolves, in which the author, Clarissa Pinkola Estes, influenced by the works of C. G. Jung, explores the myths and stories of the Wild Woman archetype. Although this is just one interpretation among the possible ones, Estes' work proves to be an interesting reading guide, as it not only contributes to the understanding of relevant aspects of Aline Bei's book - once Pequena coreografia do Adeus revisits, with its very particular style, several recurrent elements in literature -, but offers as well a psychoanalytic look at the understanding of female authorship.
Keywords: Contemporary Brazilian Literature; Aline Bei; Female authorship; Psychoanalytic theory and criticism; Archetypes